Književnodidaktične kompetence učiteljev slovenščine med študijem in prakso - Kerndl, Milena (Jezik in slovstvo, 2015)
The article presents the results of a questionnaire for third-cycle primary school Slovenian language teachers. The questionnaire is about the knowledge or competences that teachers gained during their pre-service literature training. The research demonstrates that there is a gap between the requirements of Slovenian language instruction and the expertise of new teachers, and that this gap is being reduced too slowly. In order to bridge the gap, it would be advisable for all of the institutions involved in pre- and in-service teacher training to cooperate more. Only common endeavours will contribute to a higher level of teacher expertise in quality and modern literature instruction, which would consequently lead to a culture of higher expectations in developing students' reception ability. According to research results (PISA, national examinations), the inclusion of demanding reading tasks that develop critical judgement is not yet everyday practice, which is why one should consider both the existing study programmes for future Slovenian language teachers as well as the number of special didactics lessons.
Keywords: didaktika književnosti; kompetence učiteljev; education; izobraževanje; osnovne šole